2022
DOI: 10.4103/ijn.ijn_415_21
|View full text |Cite
|
Sign up to set email alerts
|

Nell1 as Target Antigen for Mercury Related Membranous Nephropathy: A Case Report

Abstract: Membranous nephropathy constitutes 30% of adult nephrotic syndrome. Of all cases of membranous nephropathy, primary membranous nephropathy is commonest. Mercury is known to be a cause of secondary membranous nephropathy. There is no human data on the pathophysiology of mercury-related membranous nephropathy, but animal studies suggested an autoimmune mechanism behind it. There is no data to the best of our knowledge about target antigen for mercury-related membranous nephropathy. We are reporting a case of NEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Various other secondary causes have been identified, including infections, graft versus host disease, allergic reactions, and drug reactions. An interesting study reported a possible association between mercury and NELL-1-associated MN [4]. NELL-1-associated MN has also been reported in patients with HIV infection [5].…”
Section: Discussionmentioning
confidence: 89%
“…Various other secondary causes have been identified, including infections, graft versus host disease, allergic reactions, and drug reactions. An interesting study reported a possible association between mercury and NELL-1-associated MN [4]. NELL-1-associated MN has also been reported in patients with HIV infection [5].…”
Section: Discussionmentioning
confidence: 89%
“…In a rare case, the use of siddha drugs have been associated with the occurrence of MN due to the presence of mercury. In such cases, notably in a NELL1 positive patient, significant improvement was achieved by discontinuing such medication [89]. Another case report described the onset of MN in a patient due to sargramostim, a recombinant granulocyte-macrophage colony-stimulating factor (GM-CSF), who recovered completely after discontinuation [90].…”
Section: Treatment Of Secondary Membranous Nephropathymentioning
confidence: 99%